2020
DOI: 10.1111/hae.14143
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐utility analysis of emicizumab prophylaxis in haemophilia A patients with factor VIII inhibitors in Korea

Abstract: Aims Haemophilia A patients with factor VIII inhibitors (HAPI) experience frequent spontaneous bleeding, approximately once a week, and require expensive bypassing agent (BPA) treatments to control bleeding over their lifetime. According to the HAVEN 1 trial, weekly emicizumab (Hemlibra®) prophylaxis injection reduces annualized bleeding rates (ABR) by 87% compared with BPA on‐demand treatment (BPA‐OD) administered at the time of bleeding. Our study aimed to assess the cost‐effectiveness of emicizumab prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(95 reference statements)
1
11
0
1
Order By: Relevance
“…Multiple studies have shown that bleed prevention with emicizumab is more cost-effective than bypassing agents. 34,35 The introduction of Emicizumab to healthcare systems has the potential to generate additional savings by (1) delaying FVIII inhibitor development in previously untreated patients (PUPs) with the severe disease by up to 13 years, 36 (2) offering cost saving of $2 million per patient over 20 years by reducing immune tolerance induction and breakthrough bleeds, 36 (3) eliminating the need for surgical implantation of central venous access devices, especially in paediatrics and reducing severe bleeds requiring hospitalisation. The most considerable cost saving could be associated with maintaining joint health, but still, we do not know if this will be the case.…”
Section: Emicizumab Rolloutmentioning
confidence: 99%
“…Multiple studies have shown that bleed prevention with emicizumab is more cost-effective than bypassing agents. 34,35 The introduction of Emicizumab to healthcare systems has the potential to generate additional savings by (1) delaying FVIII inhibitor development in previously untreated patients (PUPs) with the severe disease by up to 13 years, 36 (2) offering cost saving of $2 million per patient over 20 years by reducing immune tolerance induction and breakthrough bleeds, 36 (3) eliminating the need for surgical implantation of central venous access devices, especially in paediatrics and reducing severe bleeds requiring hospitalisation. The most considerable cost saving could be associated with maintaining joint health, but still, we do not know if this will be the case.…”
Section: Emicizumab Rolloutmentioning
confidence: 99%
“…39 Positive results were also reported using national insurance claims and epidemiological data from Korea, as well as information obtained from the literature and from expert surveys with hematologists in that country. 40 In the study from Korea, emicizumab was found to be dominant over comparators, with predicted prevention of bleedings, QALY gains and reduced costs in base-case and sensitivity analyses. A BIA conducted considering the public healthcare system in Malaysia, concluded that the 5-year budget impact was reasonable and possibly cost-saving.…”
Section: Discussionmentioning
confidence: 98%
“…Contact activation (intrinsic pathway) Несмотря на нежелательные (НЯ) или серьезные нежелательные явления, описанные в ходе клинических испытаний [33][34][35], в реальной клинической практике, НЯ, которые привели бы к прерыванию или прекращению лечения эмицизумабом у детей зарегистрировано не было [8]. Интересно, что применение эмицизумаба при ИГА показало не только клиническую, но и экономическую эффективность в различных странах, особенно среди тех пациентов, у которых отмечалось более 10 кровотечений в год [37][38][39][40][41][42].…”
Section: Fig 1 the Main Mechanisms Of Action Of Medications For The H...unclassified